Legal Aspects of Medical Waste Management in Health Care Facilities and Protection of Environmental Health - Nurhayati, Siti; Racha, Noviati Sri (Journal of Law, Politic and Humanities, 2024)
Hazardous and Toxic Material Waste/ (Hazardous and Toxic Materials) is the residue of a business and/or activity that contains hazardous and toxic materials (B3). One of the B3 wastes is medical waste, which is infectious waste produced from activities in healthcare facilities, both in the form of solid and liquid waste. This medical waste is generated from activities such as hospitals, health centers, independent practice places, clinics, etc. facilities. Medical waste is an infectious object or item that must be managed properly, starting from the time of collection, and transportation, to the destruction process. Therefore, there needs to be legally binding regulations related to waste and its management. This research is descriptive and will produce an overview of B3 waste management regulations, especially medical waste with the protection of environmental health rights. The research approach used is a normative legal approach. The data collected is in the form of secondary data, while the analysis method used is qualitative. The results of the study show that the more human activities increase, the more waste is produced. Medical waste is one of the B3 wastes. Medical waste is waste that is directly generated from the diagnosis and treatment of patients in healthcare facilities, such as polyclinics, nursing, surgery, obstetrics, autopsies, and laboratory rooms. To avoid environmental risks, medical waste management must be done properly. Various laws and regulations for B3 waste management have been established, including Government Regulation Number 19 of 1994 (PP 19/1994) concerning Waste Management of Hazardous and Toxic Materials up to PP 101/2014. The provisions regarding B3 waste management are based on Law Number 32 of 2009 concerning Environmental Protection and Management (UUPLH). However, medical waste still needs to be synchronized with the provisions in Law Number 36 of 2009 concerning Health. Efforts to protect environmental health are carried out through the regulation and management of medical waste in healthcare facilities. Through the regulation and management of medical waste, it can prevent environmental pollution prevent the transmission of diseases (infections), and avoid the misuse of waste, so that it can maintain environmental health.